2017
DOI: 10.1017/s1742170517000424
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of exotic food crops cultivated by small-scale growers in the UK

Abstract: Exotic crops—plant species grown in relatively small quantities and not traditionally cultivated in a country or region—are often intimately linked with the ethnic origins of their maintainers and are a principal source of culinary and nutritional diversity for many people. Recognizing that a wealth of exotic crop diversity and associated knowledge is held by small-scale growers in the UK, Garden Organic initiated the Sowing New Seeds project to capture and preserve some of this valuable resource by building a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…Matrix coding query that summarizes all information obtained in this systematic review and which showed individual authors against the different benefits. Binary system where 1 shows the presence of the benefit and 0 reflects its absence (Source: the authors) [1][2][3][4]6,[8][9][10]13,14,17,23,25,27,28,. Figures 9 and 10 show that only one article mentions that there are no significant social benefits.…”
Section: Reported Challenges and Limitations From The Studies Against...mentioning
confidence: 99%
See 2 more Smart Citations
“…Matrix coding query that summarizes all information obtained in this systematic review and which showed individual authors against the different benefits. Binary system where 1 shows the presence of the benefit and 0 reflects its absence (Source: the authors) [1][2][3][4]6,[8][9][10]13,14,17,23,25,27,28,. Figures 9 and 10 show that only one article mentions that there are no significant social benefits.…”
Section: Reported Challenges and Limitations From The Studies Against...mentioning
confidence: 99%
“…Another form of NCUA are school gardens (SG), which feature vacant land on school sites designed for a range of food education-related agricultural activities involving student participation [10], which are useful for improving children's nutritional outcomes and knowledge [11], making them more willing to try unfamiliar varieties of fruits and vegetables [12]. In addition, SG provide an opportunity to meet and interact with other students in a natural environment, developing social skills, communication, and cooperation [13]. The final form of UA that is evaluated in this study is urban farms (UF), which are considered the main source of income for many urban households [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This role of small-scale growers (particularly in relation to the conservation of traditional (‘heirloom’) varieties or locally-adapted land races) is well-documented in developing countries [59,60], but has received less attention in post-industrial economies. However, even in developed countries, many small-scale producers save their own seed, and some immigrant farmers maintain more unusual crops for which local seeds may be hard to find or expensive [61,62]; the latter are therefore also being selected for locally adapted traits that may include resistance to arthropod pests and/or pathogens. In relation to these latter traits, seed saving by small-scale organic producers may be particularly important, since their crops are grown with minimal exposure to pesticides and other synthetic inputs.…”
Section: Opportunities: Factors Favoring Adoption and Development mentioning
confidence: 99%
“…e o camu-camu (Myrciaria dubia) e na mata atlantica araçá-roxo (Psidium myrtoides) são bons exemplos de frutas exóticas em Minas Gerais. Alimentos exóticos atuam no crescimento e diversificação econômica trazendo alternativas agrícolas para atender a necessidade de produtos mais saudáveis de maneira regional (Kell et al, 2017).…”
Section: Introductionunclassified